Inhibition of microbial growth by cold atmospheric plasma compared with the antiseptics chlorhexidine digluconate, octenidine dihydrochloride, and polyhexanide. Issue 4 (14th February 2019) - Langner, Inga; Kramer, Axel; Matthes, Rutger; Rebert, Farzana; Kohler, Christian; Koban, Ina; Hübner, Nils‐Olaf; Kohlmann, Thomas; Patrzyk, Maciej
Abstract : The inhibition of microbial growth is the first step toward avoiding the formation of biofilms. Therefore, this study aimed to compare the microbiostatic activity of cold atmospheric pressure plasma (CAP) with three commonly used antiseptic agents to find an alternative to or supplementary concept for antiseptic treatment. The efficacy of two CAP generating devices − the plasma jet kINPen09 ® and a hollow dielectric barrier electrode (HDBD) − both working with argon with or without admixture of 1% oxygen, was compared with chlorhexidine digluconate (CHG 0.0001 and 0.00000625%), polyhexanide (PHMB 0.0001 and 0.000025%) and octenidine dihydrochloride (OCT 0.0002 and 0.00005%). The antiseptics were added to the planktonic stage of the biofilm‐forming strains Pseudomonas aeruginosa SG 81, Staphylococcus epidermidis RP 62A, Streptococcus mutans DSM 20523 and Candida albicans ATCC 10231 resp. SC 5314. The antiseptics were present during the subsequent cultivation period (32.5 h), whereas CAP was applied for only 60 s with the same cultivation period after the exposition. During the cultivation period, growth was measured every hour by optical density and analyzed with the calculated area under the curve (AUC) to determine the delay of exponential growth. Except for the higher resistance of C. albicans against PHMB and S. mutans against CHG, P. aeruginosa was the most resistant test organism against the other antiseptic treatments. OCT 0.0002% was the most effective among the tested antiseptic agents. The plasma jet did not differ from OCT in its efficacy against C. albicans and S. mutans . Against P. aeruginosa and both Candida strains, the plasma jet was more effective than against both Gram‐positive test strains. In terms of efficacy against Candida spp., the HDBD (dielectric barrier discharge plasma) did not differ significantly from the plasma jet with argon plasma; in contrast, the bacteriostatic efficacy was significantly higher. While the addition of 1% O2 did not change the efficacy of the plasma jet, the efficacy of the HDBD against S. epidermidis increased significantly. The antimicrobial efficacy of CAP as demonstrated in earlier studies was confirmed with planktonic microorganisms showing delayed growth during cultivation for 32.5 h after a single application of CAP for 60 s. Short treatment with CAP could be an effective alternative or supplement to conventional antiseptics, for example, to inhibit the growth of microorganisms in an infected wound. OCT in the concentration used here showed the best microbial growth inhibitory results among the antiseptics. Abstract : Depended of microorganism species cold atmospheric plasma is equally or even more bacteriostatic effective against Pseudomonas aeruginosa, Staphylococcus epidermidis, Streptococcus mutans, and Candida albicans as tested common used antiseptics polyhexanide, chlorhexidine digluconate, and octenidine dihydrochloride. Therefore short treatment with plasma can be an effective alternative or supplement to conventional antiseptics to inhibit the growth of microorganisms in an infected wound.